2002
DOI: 10.1016/s0378-1119(02)01034-x
|View full text |Cite
|
Sign up to set email alerts
|

Isochore chromosome maps of the human genome

Abstract: The human genome is a mosaic of isochores, which are long DNA segments (z.Gt;300 kbp) relatively homogeneous in G+C. Human isochores were first identified by density-gradient ultracentrifugation of bulk DNA, and differ in important features, e.g. genes are found predominantly in the GC-richest isochores. Here, we use a reliable segmentation method to partition the longest contigs in the human genome draft sequence into long homogeneous genome regions (LHGRs), thereby revealing the isochore structure of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…L1B and L1C do not reside within or close to known or predicted genes, and their immediate surrounding chromatin status is unknown, although they are in regions of low guanosine plus cytosine (GC) content (39.2%) (52). For L1B, our presence͞absence PCRs in three male genomes analyzed suggest that it may have retrotransposed, carrying a 3Ј transduction.…”
Section: Discussionmentioning
confidence: 89%
“…L1B and L1C do not reside within or close to known or predicted genes, and their immediate surrounding chromatin status is unknown, although they are in regions of low guanosine plus cytosine (GC) content (39.2%) (52). For L1B, our presence͞absence PCRs in three male genomes analyzed suggest that it may have retrotransposed, carrying a 3Ј transduction.…”
Section: Discussionmentioning
confidence: 89%
“…CpG rich regions (isochores) are rich in genes and induce lower scale clustering [42][43][44][45][46].…”
Section: Exit and Recurrence Distance Distributionsmentioning
confidence: 99%
“…The different computational approaches used to disprove or redefine isochores (Eyre-Walker and Hurst 2001;Häring and Kypr 2001;Lander et al 2001;Nekrutenko and Li 2001;Cohen et al 2005) were, however, shown to be inadequate (Bernardi 2001;Bernardi 2001a,b, 2005;Li 2002;Oliver et al 2002Oliver et al , 2004Li et al 2003;Melodelima et al 2005), even if some of them led to a partial identification of isochores. This debate prompted us to map the isochores, as originally defined , in the finished sequence of the human genome (International Human Genome Sequencing Consortium 2004).…”
mentioning
confidence: 99%